The Effect of Tax Knowledge, Tax Sanctions, and Taxpayer Income Levels on Motor Vehicle Taxpayer Compliance at the Bekasi City Samsat Office in 2022-2024 - Yuyun Yuyun; Uswatun Khasanah; Maidani Maidani (Sean Institute, 2026)
This study aims to analyze the influence of tax knowledge, tax sanctions, and income levels on the compliance of motor vehicle taxpayers at the Bekasi City Samsat Office for the 2022–2024 period. The main phenomenon behind this study is the gap between the potential revenue and the realization of Motor Vehicle Tax income in Bekasi City. The research method used is a verifiable descriptive quantitative approach with a population of 4,533,569 registered vehicle owners. Sampling was carried out through simple random sampling techniques and data was analyzed using SmartPLS software version 4.0 with the PLS-SEM method. The results of the study show that tax knowledge has a positive and significant effect on taxpayer compliance. On the other hand, tax sanctions and income levels were found to have a positive but not significant effect on motor vehicle taxpayer compliance.